The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1046/j.1365-2249.1997.4411339.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nucleic acid and protein immunization for induction of antibodies specific for HIV-1 gp120

Abstract: SUMMARYWe have compared the antibody response to HIV-1 gp120 type LAI in mice immunized with either a gp120 expression plasmid or with baculovirus-derived recombinant gp120 (rgp120) formulated with Freund's complete adjuvant, TiterMax, Alum, Ribi R-700, AF-A or QuilA. DNA immunization resulted in variable levels of antibody, with endpoint titres ranging from 10 4 to 10 5 , whereas mice immunized with rgp120 mixed with Ribi R-700, AF-A or QuilA produced antibody levels with endpoint titres > 10 5 . Both types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…We observed that mice from the three strains tested (BALB/c, CBA/J, and C57BL/6) seroconverted, although an heterogeneous response was observed among mice of the same strain; and this variability was observed in repeated immunization experiments. Variations in antibody responses were also observed by other authors in inbred strains (Homan et al 1994;Haddad et al 1997;He et al 1997;Peet et al 1997;Moynier et al 1998) and they have been attributed to dierential transfection eciencies in individual mice (Haddad et al 1997). Variability in antibody levels were also observed in ts-4-vaccinated mice.…”
Section: Discussionsupporting
confidence: 64%
“…We observed that mice from the three strains tested (BALB/c, CBA/J, and C57BL/6) seroconverted, although an heterogeneous response was observed among mice of the same strain; and this variability was observed in repeated immunization experiments. Variations in antibody responses were also observed by other authors in inbred strains (Homan et al 1994;Haddad et al 1997;He et al 1997;Peet et al 1997;Moynier et al 1998) and they have been attributed to dierential transfection eciencies in individual mice (Haddad et al 1997). Variability in antibody levels were also observed in ts-4-vaccinated mice.…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, titers of IgG1 or IgG2a isotypes were heterogeneous, with some animals producing detectable levels of antigen-specific antibodies, whereas the majority appeared not to respond; this is a phenomenon already reported for other DNA vaccines (16,53). Surprisingly, B. ovis infection was unable to boost this response.…”
Section: Discussionmentioning
confidence: 56%
“…Several previously described DNA vaccines (21,26) induced antibody titers lower than that induced by the pcDNA-BLS employed in this work. This difference should be attributed to the polymeric structure of BLS.…”
Section: Resultsmentioning
confidence: 64%
“…Plasmid DNA vaccination can protect against many viral and protozoal diseases in animal models (23,26,32). The effect against bacterial infections is less well documented.…”
mentioning
confidence: 99%